Hemodynamic alterations with large spontaneous splenorenal shunt ligation during adult deceased donor liver transplantation - Chen, Guangshun; Li, Qiang; Zhang, Zhongqiang; Xie, Bin; Luo, Jing; Si, Zhongzhou; Li, Jiequn (Frontiers in Surgery, 2022)
Background: A large spontaneous splenorenal shunt (SRS) can greatly impact portal inflow to the graft during liver transplantation (LT). Direct ligation of a large SRS is an uncommon surgical method and the hemodynamic consequences of this procedure are unknown. Methods: In this retrospective study, we describe our technique for direct ligation of a large SRS and the consequent hemodynamic changes during LT. 3-Dimensional computed tomography and Doppler ultrasonography were used to evaluate SRS and intraoperative portal vein blood flow volume (PFV). Results: A total of 22 recipients had large SRS including 13 with PFV <85 ml/min/100 g (ligation group) and 9 with PFV ≥85 ml/min/100 g (no ligation group). The diameter of SRS was significantly larger in the ligation group than in the non-ligation group (22.92±4.18 vs 16.24±3.60 mm). In all ligation patients, the SRS was easily identified and isolated just below the distal pancreas and beside the inferior mesenteric vein. PV flow increased significantly from 68.74±8.77 to 116.80±16.50 ml/min/100 g (p<0.0001) after ligation; this was followed by a reduction in peak systolic velocity of the hepatic artery from 58.17±14.87 to 46.67±13.28 cm/s (p=0.0013). Conclusions: These results indicate that direct ligation of a large SRS during LT is simple, feasible, and effective.